Keteladanan Orangtua dalam Perspektif Pendidikan Islam untuk Anak - Sulaiman W.; Sulaiman Ismail (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
This article aims to elucidate the principles of parental exemplarity as an educational model from the perspective of Islamic education. The presence of parents as primary educators and central figures within the household holds significant importance. However, a fundamental challenge that arises is the lack of understanding among some parents regarding their role and responsibility as role models, which can inadvertently lead children to emulate undesirable behaviors. This research employs the